The Effectiveness of Fiscal Stimuli for Working Parents - Henk-Wim de Boer; Egbert L. W. Jongen; Jan Kabátek (Institute for the Study of Labor (IZA), 2015)
To promote the labor participation of parents with young children, governments employ a number of fiscal instruments. Prominent examples are childcare subsidies and in-work benefits. However, which policy works best for employment is largely unknown. We study the effectiveness of different fiscal stimuli in an empirical model of household labor supply and childcare use. We use a large and rich administrative data set for the Netherlands. Large-scale reforms in childcare subsidies and in-work benefits in the data period facilitate the identification of the structural parameters. We find that an in-work benefit for secondary earners that increases with income is the most effective way to stimulate total hours worked. Childcare subsidies are less effective, as substitution of other types of care for formal care drives up public expenditures. In-work benefits that target both primary and secondary earners are much less effective, because primary earners are rather unresponsive to financial incentives.
Keywords: C25; C52; H31; J22; 330; discrete choice; household labor supply; latent classes; differences-in-differences; work and care policies